(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to build physical tests - and offensive skill for the back-line players of the handball education teams. Optical vision sensor design. And finding the grades and standard levels of physical-offensive skill tests for the back-line players of the handball education teams. And to identify the level of physical performance and offensive skill of the back-line players of the handball education teams. The researcher used the descriptive approach in the survey method for its relevance to the nature of the research. The research community was determined in a deliberate way, and they are the players (handball education teams for the central and middle Euphrates regions, who are registered with the Iraqi Ministry of Education in handball) for the academic year 2021-2022, amounting to (174) players. The research sample of (160) players was adopted at a rate of (91.95%) of the total research community, and the main sample was divided into three samples according to the requirements of the study to represent the exploratory sample of (30) players, the construction sample (85) players, and the legalization sample (130) ) players (as the results of the construction sample were taken (85) players, and (45) players from the rest of the research sample). Two tests were built and codified as follows: (a test for the midfield player, and a test for the forearm player) and according to the specialization and according to the variables and difficulty that the player performs in his position, and the optical vision sensor was designed for the purpose of measuring and testing players in wider possibilities in choosing Shooting direction according to the level of difficulty that simulates the playing conditions. In light of the results obtained by the researcher through the survey and field experiment and the use of appropriate statistical methods. The researcher reached the following conclusions: - 1- The construction and codification of two physical-offensive skills tests for the back line players, they have the ability to assess the level of the players on the field using direct measurement methods. 2- Reaching a positive indicator of the two tests because more than half of the research sample got results (below and above average) 3- The two tests can be adopted as means of evaluation by coaches before, during and after the implementation of training programs to prepare the players for the back line in handball. In light of the conclusions, the researcher recommended the following: 1- Adopting the two physical tests - offensive skill to evaluate training programs in the application of different types of tactical duties, tactical diversity, and the physical capabilities of the players in the back line - offensive skill. 2- Generalizing the scores tables and standard levels for the two physical-offensive skills tests that were achieved in order to use them in the follow-up and continuous evaluation processes to know the levels and abilities of the players in the back line.